The future of beef production in America - Kiene, Fredric Arthur (My University, 1906)
Introduction: Recognizing beef production as one of the most important industries of America and one that must endure for all time, I have chosen to look into its future with thought for methods and management which shall combine to make the business of furnishing beef for the tables of the world more pleasant and profitable for the producer at the same time placing a superior product in the hands of the consumer bringing satisfaction most complete to him. The beef industry has taken its place second in importance only to the growing of cereals. It is supplementary to the grain industry in that it is a means for creating a more desirable finished product giving greater range of profit and furnishing a balance to the grain food-stuffs in the diet of man. The west primarily is the home of the beef industry although wherever corn grows and flourishes there beef production is of no small importance. Illinois, Indiana, Iowa, Missouri, Nebraska, Kansas and Oklahoma are states most prominent in this important industry for the reason that the principal feeding stuffs are numbered among their products and are most easily marketed in the shape of beef. Texas, Arizona, Colorado, Montana and Idaho, the states of the range, can only furnish the markets with cattle which may be utilized in the corn belt for the manufacture of a desirable and satisfactory finished article of diet. Thus we see twelve states actively engaged in furnishing beef to the world. An idea of the enormity of the business may be gathered from a study of the great packing plants situated at Chicago, St. Louis, Kansas City, St. Joseph and Omaha with killing capacity varying from 10,000 to 40,000 daily for each city.
Citation: Kiene, Fredric Arthur. The future of beef production in America. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Animal Husbandry; Beef; United States; Theses